Sources of international investment data in the Longitudinal Business Database - Lynda Sanderson (New Zealand Government, The Treasury, 2013)
The Longitudinal Business Database (LBD) links together firm-level data held by Statistics New Zealand from a combination of administrative and survey data sources. This linking has opened up a wide range of research opportunities. In many cases, there are now multiple sources of information on a single area of firms' activities, often capturing different aspects or a different population, requiring a choice to be made about the most appropriate source of data for any given research question. This note outlines the available firm-level data sources for research on foreign direct investment, describes the data available, and sets out some of the opportunities and challenges for using these data for research purposes. It also provides detail on maintenance procedures for one of the core elements of the LBD, the Longitudinal Business Frame, which is applicable to a wide variety of firm-level research topics.
Keywords: C81; F21; F23; 330; Foreign direct investment (FDI); Outward direct investment (ODI); Longitudinal Business Database